Kinerja Keuangan Koperasi Sebelum Dan Saat Pandemi Covid-19 Terhadap Sisa Hasil Usaha - Nur Rahmanti Ratih; Dwi Oktaviana; Miladiah Kusumaningarti (JAS (Jurnal Akuntansi Syariah), 2022)
This study analyzes the financial performance before and during the covid-19 pandemic on the operating profit. Sources of data come from primary data obtained through interviews and secondary data in the form of financial reports through documentation. The study was carried out using a quantitative descriptive method. Analysis was carried out descriptively regarding financial performance through return on assets (ROA), return on equity (ROE), and cash ratio. The study results show that financial performance before and during the covid-19 pandemic is still below cooperative financial standards and needs to produce operating profit optimally. Cooperative financial performance will have an influence on operating profit in the future. Good financial performance will be able to produce better-operating profits for cooperatives. The financial performance of cooperatives can impact obtaining profits in the future; therefore, cooperatives must manage their assets effectively and efficiently. This study can be a reference for cooperatives in running a business and increasing income.